Parents Attitude towards Heritage Language Maintenance - Dini Hidayati; Bayu Andika Prasatyo (IKIP PGRI Pontianak, 2023)
This study intends to examine parents' attitudes toward heritage languages, particularly explore strategies in maintaining the heritage language to their children. This study used qualitative research methods five parents couple are participants in this study. Data for this study were collected from participants and sources. Primary data comes from in-depth interviews with parents and supporting data comes from the questioners. In general, this study Â language is as important as Indonesian and English. The results showing that 20% of parents are in agreement and 60% of parents strongly agree with this conclusion this demonstrates parents' positive attitudes, this show that parents have positive attitude, especially in their belief in maintaining their heritage language. In maintaining the heritage language, the majority of parents use almost the same strategies where the strategies are more ordinary things, natural things that are usually done at home. such as continuing to speak the heritage language, singing folk songs, and reciting folklore in the regional language. This finding is also reinforced by questionnaire data which shows that 60% of parents introduce folk songs, tell folk tales to their children. The social environment and digital sources like TV, online games and YouTube that does not use heritage language is also an obstacle for them in maintaining heritage language because it will be influenced to use more social language than heritage language. It is also an obstacle for them in maintaining heritage language. to their children.